2016
DOI: 10.1186/s12910-016-0091-7
|View full text |Cite
|
Sign up to set email alerts
|

Making space for empathy: supporting doctors in the emotional labour of clinical care

Abstract: BackgroundThe academic and medical literature highlights the positive effects of empathy for patient care. Yet, very little attention has been given to the impact of the requirement for empathy on the physicians themselves and on their emotional wellbeing.DiscussionThe medical profession requires doctors to be both clinically competent and empathetic towards the patients. In practice, accommodating both requirements can be difficult for physicians. The image of the technically skilful, rational, and emotionall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
104
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(116 citation statements)
references
References 32 publications
2
104
1
2
Order By: Relevance
“…This may be related not only to professional, but also to academic and personal difficulties, big workload, emotional difficulties and others (Alosaimi et al, 2016;Dave et al, 2018;Ogundipe, Olagunju, Lasebikan, & Coker, 2014). Therefore, in addition to the knowledge acquired during studies, for the young doctor traits related to emotional information management and abilities that provide for effective coping with stressful situations become important (Kerasidou & Horn, 2016).…”
mentioning
confidence: 99%
“…This may be related not only to professional, but also to academic and personal difficulties, big workload, emotional difficulties and others (Alosaimi et al, 2016;Dave et al, 2018;Ogundipe, Olagunju, Lasebikan, & Coker, 2014). Therefore, in addition to the knowledge acquired during studies, for the young doctor traits related to emotional information management and abilities that provide for effective coping with stressful situations become important (Kerasidou & Horn, 2016).…”
mentioning
confidence: 99%
“…Caring behaviours have been reportedly associated with quality of worklife of those providing the care . It has been demonstrated that even physician empathy can be affected by their site (organisation) of practice . Caring behaviours of health professionals could be the result of a reciprocal exchange where those professionals feel valued by their employers …”
Section: Discussionmentioning
confidence: 99%
“…[34] It has been demonstrated that even physician empathy can be affected by their site (organisation) of practice. [35] Caring behaviours of health professionals could be the result of a reciprocal exchange where those professionals feel valued by their employers. [31] This research also found a relationship between caring behaviours and respondents' employer commitment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Relevant competences in CBT for psychologist practitioners are shown in table 1, and share 96 characteristics with those outlined by Hansen [18] and the Physiotherapy Pain Assocation [19] 97 for physiotherapists working in pain services. 98 99 [20], practitioner/therapist effects [21], attitudes and beliefs [22], empathy [23,24], and 108 other emotional responses [25]. While many physiotherapists demonstrate a positive attitude 109 and beliefs regarding PIP, they identify the need for further training to instil confidence in 110 practice [26].…”
mentioning
confidence: 99%